The Integration of Psychological and Network Perspectives in Organizational Scholarship - Casciaro, Tiziana; Barsade, Sigal G.; Edmondson, Amy C.; Gibson, Cristina B.; Krackhardt, David; Labianca, Giuseppe (Joe) (Organization Science, 2015)
Although multiple disciplines have been applied to the study of organizations, organizational research is rarely interdisciplinary in the sense of two or more disciplines being linked in the joint analysis of organizational phenomena. The articles in this special issue illustrate the kinds of insights that can be gained by moving from a purely disciplinary perspective on organizational behavior to an interdisciplinary perspective that considers network phenomena and psychological phenomena as intertwined in organizational life. The advances of this special forum notwithstanding, large swaths of network–psychological integration are still largely unexplored in organizational research. We highlight a subset of particularly promising avenues for further interdisciplinary exploration. We also observe that the two research programs have developed into distinct paradigms, making interdisciplinary discourse challenging, and offer suggestions toward a greater integration and collaboration across the two research communities.